PEMAHAMAN KONSEPTUAL TENTANG HAKEKAT MANUSIA MENURUT ALQURAN - Assa Dullah Rouf; Wedra Aprison (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This article analyzes the essence of humanity within the Qur'an. Humanity, as the finest creation of Allah, bears the responsibility of being the stewards of the Earth. There are at least five fundamental terms for 'human' translated from the Qur'an: 1. Al-Insan, 2. Al-Nas, 3. Al-Ins, 4. Al-Basyar 5. Bani Adam. The term al-insān can be connected to three aspects. Firstly, it is linked to humanity's uniqueness as stewards. Secondly, it is associated with the negative inclinations within human beings. Thirdly, it is related to the process of human creation. Insan denotes psychological or spiritual characteristics; al-nas refers to humanity as social beings; al-basyar points to humanity from a physical perspective; and Bani Adam refers to the descendants of Adam.